Omega-3 eicosapentaenoic polar-lipid rich extract from microalgae Nannochloropsis decreases plasma triglycerides and cholesterol in a real-world normolipidemic supplement consumer population - Ganuza, Eneko; Etomi, Eghogho H.; Olson, Magdalena; Whisner, Corrie M. (Frontiers in Nutrition, 2024)
Introduction: AlmegaPL ® is an oil rich in polar-lipid (>15% w/w) derived from the microalga Nannochloropsis, that contains exclusively eicosapentaenoic acid (EPA >25% w/w), without the DHA that is present in all other natural sources of omega-3. Previous findings from a randomized controlled clinical trial demonstrated the ability of AlmegaPL ® supplementation to reduce cholesterol levels.In this post-market cohort study, we built upon previous findings and targeted the actual end-users of the supplement. Participants were recruited from a new subscriber database of AlmegaPL ® capsules (1000-1100 mg/day) to capture the complexity of real-world clinical and consumer settings. Changes in circulating triglycerides (TG), remnant cholesterol (RC), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), total cholesterol (TC), high-sensitivity C-reactive protein (hs-CRP), glucose and glycated hemoglobin (HbA1c) were monitored at baseline, Month 3, and Month 6 of supplementation using the at-home Baseline Heart Health Testing Kit by Imaware ® (Houston, TX, USA).Results: Participants, who had, on average, normal TG level at baseline (1.62 ± 0.60 mmol/L), experienced a significant and progressive decrease in TG at Month 3 (8.0%; -0.13 ± 0.59 mmol/L; p<0.001) and Month 6 (14.2%; -0.23 ± 0.64 mmol/L; p<0.001) (primary outcome). Furthermore, after six months of supplementation, TC and non-HDL-cholesterol decreased by 5.0% (-0.26 ± 0.98 mmol/L; p<0.001) and 5.5% (-0.21 ± 0.86 mmol/L; p<0.001) respectively, primarily driven by a 14.9% reduction in RC (-0.11 ± 0.29 mmol/L; p<0.001).Discussion: Consistent with our previous clinical trial, the decrease in RC was not coupled to an increase in LDL, which seems to be a benefit associated with EPA-only based formulations. In addition, this study demonstrated the AlmegaPL ® capacity to maintain already healthy TG levels by further inducing a 14.9% decrease. Collectively, these findings highlight AlmegaPL ® uniqueness as a natural over-the-counter option for EPA-only polar lipid that appears particularly effective in maintaining blood lipid levels in a generally healthy, normolipidemic population.